At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure, let's find the real values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy the given equation:
[tex]\[ \frac{(1+i) x - 2i}{3+i} + \frac{(z - 3i) y + 1}{3-i} = i \][/tex]
To solve this, we initially break the equation down into more manageable steps and simplify each part carefully.
### Step-by-Step Solution:
#### 1. Simplify the terms
We start by simplifying each fraction separately.
##### Simplifying [tex]\(\frac{(1+i)x - 2i}{3+i}\)[/tex]:
Multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{((1+i) x - 2i)(3 - i)}{(3+i)(3-i)} \][/tex]
The denominator simplifies to:
[tex]\[ (3+i)(3-i) = 9 + 1 = 10 \][/tex]
The numerator simplifies to:
[tex]\[ ((1+i)x - 2i)(3-i) = (1+i)x \cdot 3 - (1+i)x i - 2i \cdot 3 + 2i \cdot i \][/tex]
[tex]\[ = 3x + 3ix - ix - x - 6i - 2i^2 \][/tex]
[tex]\[ = 3x + 2ix - x - 6i + 2 \][/tex]
[tex]\[ = (3x - x + 2ix) + (2 - 6i) \][/tex]
[tex]\[ = 2x + 2ix - 6i + 2 \][/tex]
So,
[tex]\[ \frac{2x + 2ix - 6i + 2}{10} \][/tex]
#### Simplifying [tex]\(\frac{(z-3i)y + 1}{3-i}\)[/tex]:
Multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{((z - 3i) y + 1)(3 + i)}{(3-i)(3+i)} \][/tex]
The denominator simplifies to:
[tex]\[ (3-i)(3+i) = 9 + 1 = 10 \][/tex]
The numerator simplifies to:
[tex]\[ ((z-3i) y + 1)(3 + i) = (z-3i)y \cdot 3 + (z-3i)y \cdot i + 3 + i \][/tex]
[tex]\[ = 3yz - 9iy + iyz - 3yi + 3 + i \][/tex]
[tex]\[ = 3yz + (iyz - 9iy - 3yi) + 3 + i \][/tex]
\]
So,
[tex]\[ \frac{3yz - 9iy + 3 + (iyz + i)}{10} \][/tex]
#### 2. Combine the simplified terms and equate to [tex]\( i \)[/tex]:
The simplified terms are:
[tex]\[ \frac{2x + 2ix - 6i + 2}{10} + \frac{3yz - 9iy + 3 + iy + i}{10} \][/tex]
Combining the terms:
[tex]\[ \frac{1}{10}\left(2x + 2ix - 6i + 2 + 3yz - 9iy + 3 + iy)\right) \][/tex]
[tex]\[ = 2x + 2ix - 6i + 2 + 3yz - 9iy + 3 + i \][/tex]
Since we have:
[tex]\[ 2x + 2ix - 6i + 3yz - 9iy + 2 + 1 = 6 \][/tex]
So:
[tex]\((2x + 2 + 2ix - 6i\)[/tex] + [tex]\(3yz - 9iy +1)\)[/tex])
Since the given equation simplifies to satisfying the answer:
\[
x = \frac{6}{7}, y = -\frac{31}{21}
[tex]\[ \frac{(1+i) x - 2i}{3+i} + \frac{(z - 3i) y + 1}{3-i} = i \][/tex]
To solve this, we initially break the equation down into more manageable steps and simplify each part carefully.
### Step-by-Step Solution:
#### 1. Simplify the terms
We start by simplifying each fraction separately.
##### Simplifying [tex]\(\frac{(1+i)x - 2i}{3+i}\)[/tex]:
Multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{((1+i) x - 2i)(3 - i)}{(3+i)(3-i)} \][/tex]
The denominator simplifies to:
[tex]\[ (3+i)(3-i) = 9 + 1 = 10 \][/tex]
The numerator simplifies to:
[tex]\[ ((1+i)x - 2i)(3-i) = (1+i)x \cdot 3 - (1+i)x i - 2i \cdot 3 + 2i \cdot i \][/tex]
[tex]\[ = 3x + 3ix - ix - x - 6i - 2i^2 \][/tex]
[tex]\[ = 3x + 2ix - x - 6i + 2 \][/tex]
[tex]\[ = (3x - x + 2ix) + (2 - 6i) \][/tex]
[tex]\[ = 2x + 2ix - 6i + 2 \][/tex]
So,
[tex]\[ \frac{2x + 2ix - 6i + 2}{10} \][/tex]
#### Simplifying [tex]\(\frac{(z-3i)y + 1}{3-i}\)[/tex]:
Multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{((z - 3i) y + 1)(3 + i)}{(3-i)(3+i)} \][/tex]
The denominator simplifies to:
[tex]\[ (3-i)(3+i) = 9 + 1 = 10 \][/tex]
The numerator simplifies to:
[tex]\[ ((z-3i) y + 1)(3 + i) = (z-3i)y \cdot 3 + (z-3i)y \cdot i + 3 + i \][/tex]
[tex]\[ = 3yz - 9iy + iyz - 3yi + 3 + i \][/tex]
[tex]\[ = 3yz + (iyz - 9iy - 3yi) + 3 + i \][/tex]
\]
So,
[tex]\[ \frac{3yz - 9iy + 3 + (iyz + i)}{10} \][/tex]
#### 2. Combine the simplified terms and equate to [tex]\( i \)[/tex]:
The simplified terms are:
[tex]\[ \frac{2x + 2ix - 6i + 2}{10} + \frac{3yz - 9iy + 3 + iy + i}{10} \][/tex]
Combining the terms:
[tex]\[ \frac{1}{10}\left(2x + 2ix - 6i + 2 + 3yz - 9iy + 3 + iy)\right) \][/tex]
[tex]\[ = 2x + 2ix - 6i + 2 + 3yz - 9iy + 3 + i \][/tex]
Since we have:
[tex]\[ 2x + 2ix - 6i + 3yz - 9iy + 2 + 1 = 6 \][/tex]
So:
[tex]\((2x + 2 + 2ix - 6i\)[/tex] + [tex]\(3yz - 9iy +1)\)[/tex])
Since the given equation simplifies to satisfying the answer:
\[
x = \frac{6}{7}, y = -\frac{31}{21}
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.